2016
DOI: 10.1038/ncomms11544
|View full text |Cite
|
Sign up to set email alerts
|

Most neutralizing human monoclonal antibodies target novel epitopes requiring both Lassa virus glycoprotein subunits

Abstract: Lassa fever is a severe multisystem disease that often has haemorrhagic manifestations. The epitopes of the Lassa virus (LASV) surface glycoproteins recognized by naturally infected human hosts have not been identified or characterized. Here we have cloned 113 human monoclonal antibodies (mAbs) specific for LASV glycoproteins from memory B cells of Lassa fever survivors from West Africa. One-half bind the GP2 fusion subunit, one-fourth recognize the GP1 receptor-binding subunit and the remaining fourth are spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
297
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(325 citation statements)
references
References 52 publications
23
297
0
5
Order By: Relevance
“…As a result, the identification of nAbs targeting other neutralizing epitopes is an important consideration for developing synergetic, noncompeting combinations of therapeutic anti-JUNV mAbs. Indeed, Robinson et al (36) reported a range of neutralizing epitopes among human mAbs raised upon infection by Lassa virus (LASV), a more distantly related Old World arenavirus. Of the 16 identified anti-LASV nAbs, 13 require the assembled GPC for binding, whereas 3 require only the GP1 (36).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the identification of nAbs targeting other neutralizing epitopes is an important consideration for developing synergetic, noncompeting combinations of therapeutic anti-JUNV mAbs. Indeed, Robinson et al (36) reported a range of neutralizing epitopes among human mAbs raised upon infection by Lassa virus (LASV), a more distantly related Old World arenavirus. Of the 16 identified anti-LASV nAbs, 13 require the assembled GPC for binding, whereas 3 require only the GP1 (36).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Robinson et al (36) reported a range of neutralizing epitopes among human mAbs raised upon infection by Lassa virus (LASV), a more distantly related Old World arenavirus. Of the 16 identified anti-LASV nAbs, 13 require the assembled GPC for binding, whereas 3 require only the GP1 (36). Thus, emerging techniques in mAb generation, such as the isolation of antigen-specific B cells (37) against an intact prefusion GPC spike antigen, may reveal antibodies capable of targeting alternative non-RBS epitopes on the JUNV glycoprotein surface.…”
Section: Resultsmentioning
confidence: 99%
“…Trichloroacetic acid (TCA)-precipitated pseudotyped particles were fractionated as described for biotinylated material. Protein was detected with specific antibodies directed against LASV GP2 (22.5D), kindly provided by James Robinson (Tulane University), and against VSV matrix (23H12; courtesy of Douglas Lyles; Kerafast) (56,57). Alpha-dystroglycan was detected with IIH6 monoclonal antibody (EMD Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…Since 2008, the Viral Hemorrhagic Fever Consortium (http://www.VHFC.org) has concentrated efforts at characterizing protective or pathogenic roles of B cells in LF directly from human patients (Robinson et al, 2016). This work has resulted in the derivation of the largest known collection of fully human monoclonal antibodies (huMAbs) from convalescent West African LF patients.…”
mentioning
confidence: 99%
“…A panel of 125 independently derived LASV glycoprotein-specific huMAbs were extensively characterized for binding, epitope grouping, and neutralization potential in vitro (Robinson et al, 2016). Eleven huMAbs consistently registered greater than 50% neutralization in a lentiviral entry assay system pseudotyped with the LASV (Josiah strain, Clade IV) GPC, a lymphocytic choriomeningitis virus (LCMV) backbone pseudotyped with LASV GPC, or in a live LASV plaque reduction neutralization test (PRNT) (Robinson et al, 2016).…”
mentioning
confidence: 99%